South Africa - Constraints to Growth and Employment : Evidence of the Small, Medium and Micro Enterprise Firm Survey - World Bank (Washington, DC, 2013)
This report identifies several themes that cover both macroeconomic constraints as well as structural factors affecting small, medium, and micro enterprises (SMME) in South Africa. After the introduction, Chapter 2 continues to discuss firm demographics for the 800 SMME firms surveyed. Characteristics such as age, race, size, and legal status of the firm are presented along with a brief description of the entrepreneurs' motivations for starting their SMME. Chapter 3 provides information on the degree to which firms in this survey have been expanding or contracting employment and investment levels, followed by a discussion of factors limiting further expansion. This section of the report also contains ratings indicating the policies SMME firms would like local and national governments to implement or improve. The remaining chapters contain more detailed analyses of each of the main constraints identified. Chapter 4 discusses the skills shortage as well as the degree to which SMME firms are hindered by inflexible labor arrangements. Chapter 5 analyzes the capital constraints, but with regard to access and cost. Chapter 6 illustrates the insufficient progress made by government promotion and procurement programs. Chapter 7 discusses the business environment within which SMME firms must operate, paying particular attention to location ratings and crime. Finally Chapter 8 evaluates the extent to which the SMME tier is linked to the international economy.